Impact of Amino-Alcohol Organic Molecule on Various Silicon Oxide Bondings. (16th June 2021) - Calvez, A.; Fournel, F.; Larrey, V.; Eleouet, G.; Morales, C.; Rieutord, F.
Abstract : Recently a new surface preparation method using an organic molecule was introduced for silicon direct wafer bonding F. Fournel, L. Continni, C. Morales, J. Da Fonseca, H. Moriceau, F. Rieutord, A. Barthelemy, and I. Radu, J. Appl. Phys., 111, 104907 (2012). Adding a very small amount of amino-alcohol molecule at the bonding interface drastically increased the bonding energy after low post bonding annealing temperature. In this study, additional developments using the same molecule type (DEAE: N-N-diethylaminoethanol) are presented.